Envisioning the Future of Islamic Studies Scholarship: Liberation, Healing, and Sustainability - Nayawiyyah Muhammad (Global Journal of Human-Social Science, 1970)
There are striking interconnections between the dominations of all kinds with linking attitudes and consequences Whether it is a matter of religion gender race ethnicity class or even species everything is interconnected Globally the most disadvantaged populations are marginalized Since religion is a meaningful way whereby the roles of the present and future generations are defined and imposed this article offers an investigation and analysis of current global issues surrounding environmental ruin and social inequality by highlighting the role of Islamic Studies scholarship A vision of future scholarship in Islamic Studies and the perceived shifting times is presented in three parts identification explanation and solution Liberation healing and sustainability are the proposed solutions and outcomes for resolving current problems within an interpretation of Islam s sacred texts In this regard scholarship can make a significant contribution in challenging misconceptions that promote dominance oppression and violence